Members of Gammaproteobacteria as indicator species of healthy banana plants on Fusarium wilt-infested fields in Central America - Koberl, M.; Dita, M.; Martinuz, A.; Staver, Charles; Berg, G. (Springer, 2017)
Culminating in the 1950’s, bananas, the world’s most extensive perennial monoculture, suffered one of the most devastating disease epidemics in history. In Latin America and the Caribbean, Fusarium wilt (FW) caused by the soil-borne fungus Fusarium oxysporum f. sp. cubense (FOC), forced the abandonment of the Gros Michel-based export banana industry. Comparative microbiome analyses performed between healthy and diseased Gros Michel plants on FW-infested farms in Nicaragua and Costa Rica revealed significant shifts in the gammaproteobacterial microbiome. Although we found substantial differences in the banana microbiome between both countries and a higher impact of FOC on farms in Costa Rica than in Nicaragua, the composition especially in the endophytic microhabitats was similar and the general microbiome response to FW followed similar rules. Gammaproteobacterial diversity and community members were identified as potential health indicators. Healthy plants revealed an increase in potentially plant-beneficial Pseudomonas and Stenotrophomonas, while diseased plants showed a preferential occurrence of Enterobacteriaceae known for their plant-degrading capacity. Significantly higher microbial rhizosphere diversity found in healthy plants could be indicative of pathogen suppression events preventing or minimizing disease expression. This first study examining banana microbiome shifts caused by FW under natural field conditions opens new perspectives for its biological control.